Informe sobre siembra y evaluacion de germinacion de las parcelas sembradas en Mondomo (Cauca) en mayo de 1979 por el Programa de Economia de Yuca : Proyecto conjunto de ensayo y validacion de tecnologia (CIAT-ICA) - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
In Mondomo, state of Cauca (Colombia), a socioeconomic survey was made of the 7 famers in the area that participated in the program of demonstration plots. In general terms the educational level is varied, the majority (6) are full-time farmers who have lived in the area greater than 10 yr and have an equal amount of experience in cassava cultivation. The av family size is 5 people, of whom 3 are of an economically active age. Av farm size is 15.12 ha. Cassava is the most important crop extensionwise, followed by coffee, Six farmers use credit facilities. Two evaluations were made on the percentage of sprouting, weeds and insects present in the plots: the 1st, 30 days after planting and the 2nd, at 60 days. In both, the percentage of sprouting was greater than 90 percent; CM 323-375 was the most promising vu. with the best percentage; the var. Algodona had the greater than percentage of sprouting among the regional var. There was no statistical difference in the sprouting among var. due to the treatment of the cuttings. The plots were generally found to be weed-free. When evaluating pest incidence, whiteflies, hornworm eggs and larvae, and thrips were found, but with very low densities/plant. (CIAT)